The welfare systems of the Baltic states following the recent financial crisis of 2008–2010: expansion or retrenchment?. Issue 1 (2nd January 2019) - Aidukaite, Jolanta
ABSTRACT: This article aims to uncover major social security system reforms that were implemented following the recent financial and economic crisis of 2008–2010 and the post crisis period. Additionally, it explores the dynamics of the socioeconomic situation during the last 10 years, looking at how Baltic states compare with each other and how they compare with other central and eastern European countries in the EU. The findings show that retrenchment is difficult even during times of crisis. Although the Baltic states were affected by the crisis, especially Latvia and Lithuania, their social security institutions did not experience any structural shift.